Healthy diet: Health impact, prevalence, correlates, and interventions. Issue 8 (3rd August 2017) - de Ridder, Denise; Kroese, Floor; Evers, Catharine; Adriaanse, Marieke; Gillebaart, Marleen
Abstract : Objective: To discuss healthy diet from a psychological perspective by considering definitions of healthy diet in terms of consumer understanding; the health effects of specific dietary elements in terms of overweight and (chronic) illness; the prevalence of healthy diet; the psychological and environmental determinants of healthy diet; and the psychological interventions that have been designed to promote healthy diet. Design: A systematic review of the psychological literature on healthy diet. Results: Our findings suggest that consumers have a relatively poor understanding of a healthy diet. The literature also demonstrates that there is poor evidence on the health protective effects of single foods or nutrients. We further show that low SES is the single consistent risk factor for not adhering to a healthy diet. Our review of the literature on determinants demonstrates that intentions, habits, self-regulatory skills, and the social and physical environment are the most important determinants of a healthy diet, which are in turn amenable to change by intervention strategies with varying levels of effectiveness. Educational interventions generally show a limited effect on practising a healthy diet whereas interventions targeting habitual behaviour and/or the physical environment seem more promising. Conclusions: In view of the large number of people who are concerned about their diets and make attempts to change their dietary patterns, we conclude that it is crucial to gain a better understanding of both the automatic and environmental influences that are responsible for people not acting upon their good intentions for diet change.